Aspects of pharmaceutical care for patients with cephalgia in specialized neurology clinics - O. V. Reshetko; A. I. Grishin; R. R. Parsamyan; E. A. Rakhmanova (Реальная клиническая практика: данные и доказательства)
Objective. To determine the characteristics of pharmaceutical care for patients with headache in specialized neurology clinics.Materials and methods. Questionnaire survey of clinic patients with the integrated ID–Migraine test using a validated questionnaire (from August to October 2023 inclusive) by a continuous sampling method, statistical processing of the results. Descriptive statistics and parametric and nonparametric methods were used in the statistical processing. The initially established level of statistical significance was considered to be at least 95 % at p <0.05.Results. The study was conducted until 100 completed questionnaires were received. There was a high prevalence of women (84.0 %), mostly older than 40 years (68.1 %, n=94), and the average age of patients was 49.4±1.5 years. Migraine as a cause of headache was stated by 21.0 % of patients, and 38.9 % of patients answered positively to two or more questions of the ID–Migraine test (n=98), which may indicate the presence of migraine. Self-medication is widespread among patients (78.0 %), with 71.0 % considering it necessary to consult a physician only in case of prolonged headache that does not go away with analgesics. 63.0 % consider pharmacy as a specialized organization and pharmacists as highly qualified specialists who can qualitatively advise customers on drugs and symptoms, but should not diagnose and should not replace a physician (100.0 %). Also, the majority (72.0 %) believe that no pharmacist should be able to diagnose the type of headache based on symptoms and recommend drugs accordingly. Among the most important factors (on a 3‑point scale) influencing drug choice, clinic patients mentioned proven efficacy and safety (2.45±0.09), and prescribing physician (2.45±0.09). This indicates high compliance and trust of the clinic patients in the physician. The results of the questionnaire revealed three «profiles » of patients, the basis of which being fundamentally different attitudes toward pharmacists, pharmacies and physicians: neutral (loyal to pharmacies and pharmacists), highly loyal (to pharmacies and pharmacists), and loyal to the physician.Conclusion. Patients in clinics may be represented by different subgroups with specific characteristics, needs, preferences, and, accordingly, different strategies of pharmaceutical care. This highlights the need for an individualized approach to communication between the pharmacists and each patient, considering the specificity of their needs and expectations.